New realizations of N=2 l-conformal Newton-Hooke superalgebra; Modern Physics Letters A; Vol. 30, iss. 13 - Masterov I. V. Ivan Viktorovich (Particles and Fields; Gravitation; Cosmology and Nuclear Physics, 2015)
Title screen